New sorghum hybrids for Southern Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Farmers in Southern Africa will soon have the opportunity to grow higher yielding hybrids of sorghum. In low rainfall areas these new hybrids are outyielding hybrid maize by more than 50%. At the moment hybrid maize usually gives better yields, even...